2021
DOI: 10.1021/acs.nanolett.0c04833
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Janus Particles as Multivalent Synthetic Nanoparticle Antibodies (SNAbs) for Selective Depletion of Target Cells

Abstract: Monoclonal antibodies (mAb) have had a transformative impact on treating cancers and immune disorders. However, their use is limited by high development time and monetary cost, manufacturing complexities, suboptimal pharmacokinetics, and availability of disease-specific targets. To address some of these challenges, we developed an entirely synthetic, multivalent, Janus nanotherapeutic platform, called Synthetic Nanoparticle Antibodies (SNAbs). SNAbs, with phage-display-identified cell-targeting ligands on one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…In order to circumvent the immunosuppressive TME caused by MDSCs, Liu et al constructed an entirely synthetic, multivalent, Janus nano-therapeutic platform called synthetic nanoparticle antibodies (SNAbs), which is a type of MDSC-targeting NPs for the effective depletion of MDSCs in TME. 68 In contrast to other cell types in TME, MDSCs express tenfold higher cell surface S100A8/A9 proteins, and either G3 peptide or G3* peptide conjugated in the NPs shows excellent binding affinity to S100A8/A9 proteins. In vitro and in vivo experiments based on 4T1 mouse breast cancer model demonstrated that this NPs significantly reduced the viability and the total amount of MDSCs.…”
Section: Nanoparticles Remodel Tumor Microenvironment Through Immunoregulatorymentioning
confidence: 94%
“…In order to circumvent the immunosuppressive TME caused by MDSCs, Liu et al constructed an entirely synthetic, multivalent, Janus nano-therapeutic platform called synthetic nanoparticle antibodies (SNAbs), which is a type of MDSC-targeting NPs for the effective depletion of MDSCs in TME. 68 In contrast to other cell types in TME, MDSCs express tenfold higher cell surface S100A8/A9 proteins, and either G3 peptide or G3* peptide conjugated in the NPs shows excellent binding affinity to S100A8/A9 proteins. In vitro and in vivo experiments based on 4T1 mouse breast cancer model demonstrated that this NPs significantly reduced the viability and the total amount of MDSCs.…”
Section: Nanoparticles Remodel Tumor Microenvironment Through Immunoregulatorymentioning
confidence: 94%
“…Synthetic Nanoparticle Antibodies (SNAbs) were developed to efficiently deplete MDSCs. The systemic injection of MDSC-targeting SNAbs in a mouse triple-negative breast cancer model was affirmed to selectively lower the circulating MDSCs and promote T cell and NK cell infiltration into the tumor [ 152 ].…”
Section: Mdscs In Murine Models Of Solid Tumorsmentioning
confidence: 99%
“…168,169 For elimination of MDSCs, a study has found that systemic injection of MDSC-targeting multivalent synthetic nanoparticle antibodies (SNAbs) can efficiently deplete circulating MDSCs in a mouse triple-negative breast cancer model, enabling enhanced T cell and NK cell infiltration into tumors. 170 It has been found that intravenous administration of cargo-free PLGA nanoparticles can result in internalization by MDSCs and monocytes. Combined with the anti-PD-1 antibody, these cargo-free PLGA nanoparticles have been found to significantly decrease the abundance of MDSCs in the circulation and in the lungs, and slow tumor growth and result in a survival benefit in the 4T1 mouse model of metastatic triple-negative breast cancer.…”
Section: Nanoparticles For Modulating Mdscsmentioning
confidence: 99%